Can liver cirrhosis patients benefit from target controlled infusion of propofol for conscious sedation during endoscopic variceal ligation? - Li, Jun-Xiang; Wu, Jun-Chao; Lin, Wei-Wei; Wang, Xiao (International Surgery Journal, 2017)
Background: The aim of the present study was to evaluate the feasibility of conscious sedation using target controlled infusion of propofol combined with a single dose of fentanyl during endoscopic variceal ligation in patients with liver cirrhosis. Methods: Forty-eight patients with liver cirrhosis scheduled for endoscopic variceal ligation were randomly assigned to deep sedation group (DS group) with intravenous bolus of propofol and conscious sedation group (CS group) with target controlled infusion of propofol, 1 μg/kg fentanyl was intravenously injected in each patient before administration of propofol. Cardiorespiratory parameters were monitored, and the side-effects were recorded. The depth of sedation was assessed by both of the sale of observer′s assessment of alertness/sedation (OAA/S) and the bispectral index (BIS). The quality of sedation/analgesia was evaluated by the endoscopist and patients using Visual Analog Scores (VAS). The recovery level was evaluated with the Aldrete scales. Results: No significant differences were found on demographic data and initial parameters in the two groups. Compared with the CS group, the changes of mean arterial pressure (MAP) and heart rate (HR) and the signs of respiratory depression were significant in the DS group (p<0.05). The recovery time in DS group (16.7±2.7 minutes) was much longer than that in the CS group (9.3±3.0 minutes, p<0.01). There was no difference in Visual Analogue Scale scores for endoscopist’s satisfaction between the two groups (9.2±0.6 versus 9.0±0.6, p>0.05), but a higher degree of satisfaction for patient was found in the DS group (9.3±0.6 versus 7.9±0.7, p<0.01). Conclusions: Conscious sedation with target controlled infusion of propofol combined with a single bolus of fentanyl for endoscopic variceal ligation in patients with liver cirrhosis had better hemodynamic stability, less respiratory depression and shorter recovery time.